The impact of ambivalence on recovery from non-suicidal self-injury: considerations for health professionals - Gray, Nicole; Hasking, Penelope; Boyes, Mark (2021)
Purpose: Non-suicidal self-injury (NSSI) is a growing public health concern. Continued NSSI is often associated with negative outcomes, yet the behaviour usually serves a purpose for individuals who self-injure (e.g. emotional relief). As such, individuals who self-injure often experience ambivalence about the behaviour. The purpose of this paper is to highlight the importance of recognising ambivalence as a natural and expected part of the recovery process. Design/methodology/approach: This paper draws on literature regarding NSSI recovery, ambivalence towards stopping the behaviour and challenges for both clients and health professionals. Findings: This paper argues that ambivalence towards self-injury can be challenging for both clients and health professionals. Clients may feel shame and sense of failure if they experience a setback; health professionals may experience frustration towards clients who continue to self-injure despite treatment. Originality/value: Validation of the clients’ experience can have significant positive outcomes in treatment and help-seeking behaviours. Acknowledgement of client ambivalence during the recovery process will serve to validate clients’ experience and facilitate rapport. Health professionals who accept ambivalence as a natural part of the recovery process may experience less frustration with clients who continue to self-injure.